Using Collaborative Instructional Approach to Improve Mathematics Achievement of Students with Openness to Experience Traits During Pandemic Era in Taraba State - Yukwa, Bernard A.; Nshie, Fai M. (Darul Yasin Al Sys, 2024)
This paper focuses on the Influence of Collaborative Instructional Approach on Mathematics Achievement of Students with Openness to Experience Traits during Pandemic Era in Taraba State. Qualitative Research Design was adopted whereby data were gathered through secondary sources. Findings revealed that during the Pandemic Era, students with Openness to Experience enjoyed learning when they were exposed to Collaborative Instructional Approach. It was recommended that teachers should be encouraged to group students based on student’s personal traits to improve their achievement during the Pandemic Era in Taraba State.